Bioethical Responsibility towards Current and Future Generations (Part II) - Kugler, Gerlinde (Studia Bioethica, 2018)
The present work provides a theoretical and applied reflection on bioethical responsibility towards current and particularly future generations. After having introduced interrelated key concepts, two partly opposite views will be substantiated by arguments grounded in various realities of human life. The resulting synthesis will aim at reaching the most profound source for man’s real responsibility (Part I). For this purpose, an anthropologically guided path will ultimately lead to the reality of love (Part II). The subsequent applicative part will translate all insights gained to bioethical responsibility within the development and lifecycle of a new medicinal product. More specifically, focus will be laid on two key aspects therein, namely the performance of mandatory clinical trials in the paediatric population and safety monitoring of medicinal products. Overall, this work is intended as sound support to discover and to effectively realise one’s own bioethical responsibility.